Series elasticity facilitates safe plantar flexor muscle–tendon shock absorption during perturbed human hopping - Dick, Taylor J. M. (Proc Biol Sci, 2021)
In our everyday lives, we negotiate complex and unpredictable environments. Yet, much of our knowledge regarding locomotion has come from studies conducted under steady-state conditions. We have previously shown that humans rely on the ankle joint to absorb energy and recover from perturbations; however, the muscle–tendon unit (MTU) behaviour and motor control strategies that accompany these joint-level responses are not yet understood. In this study, we determined how neuromuscular control and plantar flexor MTU dynamics are modulated to maintain stability during unexpected vertical perturbations. Participants performed steady-state hopping and, at an unknown time, we elicited an unexpected perturbation via rapid removal of a platform. In addition to kinematics and kinetics, we measured gastrocnemius and soleus muscle activations using electromyography and in vivo fascicle dynamics using B-mode ultrasound. Here, we show that an unexpected drop in ground height introduces an automatic phase shift in the timing of plantar flexor muscle activity relative to MTU length changes. This altered timing initiates a cascade of responses including increased MTU and fascicle length changes and increased muscle forces which, when taken together, enables the plantar flexors to effectively dissipate energy. Our results also show another mechanism, whereby increased co-activation of the plantar- and dorsiflexors enables shortening of the plantar flexor fascicles prior to ground contact. This co-activation improves the capacity of the plantar flexors to rapidly absorb energy upon ground contact, and may also aid in the avoidance of potentially damaging muscle strains. Our study provides novel insight into how humans alter their neural control to modulate in vivo muscle–tendon interaction dynamics in response to unexpected perturbations. These data provide essential insight to help guide design of lower-limb assistive devices that can perform within varied and unpredictable environments.